2015
DOI: 10.4306/pi.2015.12.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Cut-Off Scores of the Children's Depression Inventory for Screening and Rating Severity in Korean Adolescents

Abstract: ObjectiveThe aim was to establish an optimal cut-off score of the Children's Depression Inventory (CDI) for detecting depression and rating severity in Korean adolescents.MethodsA total of 468 students aged 12-16 years from 8 middle schools in Busan, Korea participated in this study. The Korean version of the CDI and Kiddie Schedule for Affective Disorders and Schizophrenia Present and Lifetime Version were used to evaluate depressive symptoms. Receiver-operating characteristics (ROC) analyses were conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 21 publications
(29 reference statements)
2
51
0
1
Order By: Relevance
“…The Korean version of the Children’s Depression Inventory (CDI) was used to assess depressive symptoms in children with ADHD. A CDI sum score of 20 was identified as the optimal screening cut-off score, for which the sensitivity was 0.83 and the specificity was 0.89 in Korean adolescents 29). We also assessed participants using the Korean Internet Addiction Self-scale (K-scale), with total K-scale scores representing the severity of problematic internet use.…”
Section: Methodsmentioning
confidence: 99%
“…The Korean version of the Children’s Depression Inventory (CDI) was used to assess depressive symptoms in children with ADHD. A CDI sum score of 20 was identified as the optimal screening cut-off score, for which the sensitivity was 0.83 and the specificity was 0.89 in Korean adolescents 29). We also assessed participants using the Korean Internet Addiction Self-scale (K-scale), with total K-scale scores representing the severity of problematic internet use.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate greater depression severity, with raw scores of 15, 21, and 25 reflective of mild, moderate, and severe depression, respectively (Bang, Park, & Kim, 2015). For the purposes of this study, raw scores were transformed to age and sex corrected T-scores with a mean of 50 and a standard deviation of 10.…”
Section: Methodsmentioning
confidence: 99%
“…This scale evaluate 6 subscales including negative mood, interpersonal problems, ineffectiveness, anhedonia and negative selfesteem (11). The cut-off point for CDI reported as 15 for mild, 20 for moderate and 25 for severe depression (2). The CDI has shown adequate reliability and validity in previous studies; previous studies reported high internal consistency with a Cronbach's α of 0.82 (12) and 0.86 (13).…”
Section: Children's Depression Inventory (Cdi)mentioning
confidence: 99%
“…Two-thirds of adolescents with depression also suffer from at least one other psychiatric disorder such as anxiety disorders, attention deficit hyperactivity disorder (ADHD), conduct disorder, and substance abuse disorder. Depressed adolescents are also at higher risks of academic failure, interpersonal problems, and suicidal tendencies (2).…”
Section: Introductionmentioning
confidence: 99%